Palace, mosque, and tomb at al-Ruwayḍah, Qatar - Petersen, Andrew; Grey, Anthony (Proceedings of the Seminar for Arabian Studies, 2012)
This paper discusses the results of recent excavations and survey at al-Ruway< Jah in northern Qatar. The main elements of the site that are discussed in detail are the excavations of a palace, a mosque, and a tomb. In addition, there is a report on the ceramics recovered from the excavations and a discussion of the significance and potential of the excavated areas.